Anaemia can be improved by controlling the disease activity of Takayasu's arteritis without iron administration. (19th September 2022) - Guo, Yanqiu; Du, Juan; Li, Taotao; Gao, Na; Pan, Lili
Abstract: Background: Anaemia is a common clinical manifestation observed in Takayasu's arteritis (TAK), but few studies have been conducted. This study investigated whether improvement of inflammatory indicators was associated with improvement of anaemia in TAK. We also investigated whether iron supplement treatment could benefit in addition to immunosuppressant therapy in the anaemia patients with TAK. Methods: This was a retrospective cohort study of 160 patients diagnosed with TAK. All patients were further assigned into anaemia group (67 cases) or non‐anaemia group (93 cases) according to their haemoglobin levels. Fifty two anaemia patients completed follow‐up (median 5.2 months). Results: There were 67 (41.88%) anaemia patients among all 160 TAK patients. Compared to TAK patients without anaemia, the average age [32 (24, 45) vs. 40 (31, 48), p = 0.002], disease duration [36 (7, 120) vs. 72 (14, 162), p = 0.017] and BMI [21.43 (18.96, 23.81) vs. 22.86 (20.09, 25.81), p = 0.008] were significantly lower in TAK patients with anaemia. The levels of ESR [23 (15, 51) vs. 11 (5.5, 22), p = 0.0001] and CRP [9.33 (1.99, 27.8) vs. 1.99 (0.45, 6.68), p = 0.0001] were significantly increased in TAK patients who complicated with anaemia. After follow‐up, decrease of ESR, CRP and disease activity score (NIH and ITAS) were significantly associated with improvement of anaemia. One unit decrease of ESR and CRP, the hazard ratio of the improvement rate of anaemia was 1.02 [95% CI (1.00, 1.03); p = 0.027] and 1.04 [95% CI (1.02, 1.07); p < 0.001] respectively. One point decrease of NIH and ITAS‐A was associated with a higher probability of anaemia improvement [HR 95% CI: 1.25 (1.02, 1.41), p = 0.022, HR 95% CI: 1.62 (1.21, 2.17), p = 0.001]. These relationships were consistent between iron supplement treatment group and without iron supplement treatment group. We found no significant difference in cumulative hazard between the two groups ( p = 0.692). Conclusion: Anaemia was a common complication in TAK. Decrease of ESR, CRP and disease activity score (NIH and ITAS) were significantly associated with improvement of anaemia, even after adjusting for various covariates. Moreover, these relationships were consistent between iron supplement treatment group and without iron supplement treatment group. There was no significant difference in the improvement of anaemia in patients receiving immunosuppressant therapy with or without iron supplement treatment.